2001
DOI: 10.1029/2000jd900579
|View full text |Cite
|
Sign up to set email alerts
|

A study of the reaction between NaHCO3 and H: Apparent closure on the chemistry of mesospheric Na

Abstract: Abstract. The reaction between sodium bicarbonate (NaHCO3) and atomic H is the only likely route (apart possibly from daytime photolysis) for recycling this major sodium reservoir back to atomic Na in the upper mesosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 14 publications
1
63
0
Order By: Relevance
“…In contrast, this reaction has a large activation energy (Cox et al, 2001); that is, at higher temperatures it becomes much faster, and the steady-state balance shifts from NaHCO 3 to Na. A secondary effect is that O 3 forms from the recombination of O and O 2 , and this reaction gets slower at higher temperatures: the result is that smaller O 3 concentrations slow down the conversion of Na to NaO, and the larger O concentrations reduce NaO back to Na, enhancing the effect of Reaction (4) becoming faster.…”
Section: Global Latitudinal and Seasonal Variationsmentioning
confidence: 98%
“…In contrast, this reaction has a large activation energy (Cox et al, 2001); that is, at higher temperatures it becomes much faster, and the steady-state balance shifts from NaHCO 3 to Na. A secondary effect is that O 3 forms from the recombination of O and O 2 , and this reaction gets slower at higher temperatures: the result is that smaller O 3 concentrations slow down the conversion of Na to NaO, and the larger O concentrations reduce NaO back to Na, enhancing the effect of Reaction (4) becoming faster.…”
Section: Global Latitudinal and Seasonal Variationsmentioning
confidence: 98%
“…The sodium column abundance reaches a maximum during the period of (JulyAugust), and a minimum around (February-January). Several authors, such Cox et al (2001), Xiong et al (2003), and Drummond et al (2007) noted that the time evolution of the mesospheric sodium column abundance has a characteristic period of one year. It is tempting to suggest that the maximum of the sodium column abundance could be explained by the increase in the meteoric input during this period, which is rich in terms of meteor showers.…”
Section: Column Abundancementioning
confidence: 99%
“…The chemical reactions responsible for the conversion of Na to NaHCO 3 occur rapidly and have small temperature dependencies (Plane 2004(Plane , 1998. NaHCO 3 is converted back to Na by the reaction with H. This reaction has a large activation energy, that is at higher temperatures it becomes much faster, and the steady-state balance shifts from NaHCO 3 to Na (Cox et al 2001). It was suggested that the final sink for sodium on the bottomside of the layer is attachment to aerosol particles (Hunten et al 1980).…”
Section: Mesospheric Sodium Layer Chemistrymentioning
confidence: 99%
“…Note that according to these quantum calculations the dimer should be a sink for sodium, because it will not photolyse at wavelengths above 180 nm, nor react with atomic H (in constrast to NaHCO 3 , Cox et al, 2001;Self and Plane, 2002). In NAMOD, the concentrations of the three major gasphase sodium species, Na, NaHCO 3 and Na + , are determined by full solution of their respective continuity equations.…”
Section: Sodium Chemistrymentioning
confidence: 99%